S94 A Prospective Study Investigating Oral Corticosteroid (ocs) Use And Quality Of Life In Omalizumab Treated Severe Allergic Asthma Patients – Results From An Interim Analysis Of The Apex Ii Study. (10th November 2014) - Chaudhuri, R; Menzies-Gow, A; Khachi, H; Hand, S; Gore, R; Niven, R
Abstract : Background: A previous retrospective study of UK clinical practice demonstrated that omalizumab reduced OCS burden. Aim: This multi-centre observational study was conducted to confirm the observed retrospective findings prospectively. Methods: Retrospective data were collected in the 12 months prior to omalizumab, while prospective data were collected at 16 weeks, 8 and 12 months following initiation. The primary endpoint was the change in mean daily OCS dose in the 12 months pre and post omalizumab initiation. Secondary endpoints included changes in ACT and AQLQ scores in the 12 months pre and post omalizumab initiation. Results: 235 patients were enrolled by the end December 2013 in 22 UK centres. Data for interim analysis were examined from patients who had 12 months assessment at database lock (n = 85, 54% females, mean (±SD) age 44 yr (±13.2), mean (±SD) duration of asthma 26 yr (±14.0)). At the 16 weeks assessment 74/85 (87%) patients were classified as responders to omalizumab treatment. At 12 months, mean daily OCS dose decreased by 25% (n = 85, p < 0.001) from 10.77 mg/day (±7.87) to 8.08 mg/day (±8.39) and 55% (n = 46/84) of patients stopped OCS. 71% (n = 60/85) of patients stopped or reduced OCS by ≥20%. Comparing the 12 months periods prior to and following initiation of omalizumab, the mean ACT score improved from 9.8 (±4.8) to 14.2 (±5.2) (n = 75, p < 0.001) and the mean AQLQ score improved from 3.1 (±1.3) to 4.3 (1.46) (n = 60, p < 0.001) [Graph 1 ]. Conclusions: The data prospectively confirms that omalizumab is associated with statistically and clinically significant reduction in OCS and statistically and clinically significant improvement in asthma symptom control and quality of life.